Liquid and firm sourdough fermentation: microbial robustness and interactions during consecutive backsloppings. (May 2019) - Galli, Viola; Venturi, Manuel; Pini, Niccolò; Guerrini, Simona; Granchi, Lisa; Vincenzini, Massimo
Abstract: This study investigated the establishment of wheat stable sourdoughs, both in liquid (dough yield = 330) and firm (dough yield = 154) conditions, by inoculating 5 strains of different lactic acid bacteria species together with either a Saccharomyces cerevisiae or a Candida milleri strain. Real propagation cycles, consisting of ten refreshments, were simulated to assess the behaviour and robustness of the microorganisms. The results indicated stable microbial communities from seventh backslopping in all the tested conditions, with some differences among the strains. Lactobacillus farciminis Lf19 proved to be the most competitive strain, maintaining high concentrations throughout the refreshments at different dough yield, while Lactobacillus rossiae Lr9 resulted the less performing strain. Due to the longer refreshment time (24h instead of 6h) and to the presence of Saccharomyces cerevisiae, Lactobacillus sanfranciscensis Ls51 was probably affected by the maltose depletion in liquid condition. At sourdoughs stability, the main technological characteristics (pH, total titratable acidity, fermentation quotient) were in agreement with those reported for mature sourdoughs. Overall, this study evaluated the effect of modifying some parameters (dough yield, refreshment time, associated yeast, etc.) on microbial composition and on sourdough main features, to select the most suitable sourdough technology to be used. Highlights: Ten consecutive backsloppings, both in firm and liquid conditions, were carried out. Lactobacilli behaviour depended on dough yield, refreshment time and associated yeast. Maltose depletion mostly affected Lactobacillus sanfranciscensis Ls51 robustness. Lactobacillus rossiae Lr9 was the less performing strain in all the tested conditions. Lactobacillus farciminis Lf19 was the most competitive strain in all the conditions.